2019
DOI: 10.3390/ma12101707
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Concrete Containing Graphene Oxide Nanosheets

Abstract: Concrete made from ordinary Portland cement is one of the most widely used construction materials due to its excellent compressive strength. However, concrete lacks ductility resulting in low tensile strength and flexural strength, and poor resistance to crack formation. Studies have demonstrated that the addition of graphene oxide (GO) nanosheet can effectively enhance the compressive and flexural properties of ordinary Portland cement paste, confirming GO nanosheet as an excellent candidate for using as nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…The results have demonstrated that the addition of GO nanosheet reduced the flowability of UHPC mixture with high volume SCMs and thus its workability. Similar results were also reported in previous studies on NC [20,21], UHSC [22], self-compacting ultra-high-performance cement-based composites with high cement content [24], all containing GO nanosheets. Elsewhere, a previous study regarding UHPC enhanced with the graphite nanoplatelet (GNP), which is another…”
Section: Effect Of Go Nanosheets On Fluidity Of Uhpc Mixture With High Volume Scmssupporting
confidence: 90%
See 3 more Smart Citations
“…The results have demonstrated that the addition of GO nanosheet reduced the flowability of UHPC mixture with high volume SCMs and thus its workability. Similar results were also reported in previous studies on NC [20,21], UHSC [22], self-compacting ultra-high-performance cement-based composites with high cement content [24], all containing GO nanosheets. Elsewhere, a previous study regarding UHPC enhanced with the graphite nanoplatelet (GNP), which is another…”
Section: Effect Of Go Nanosheets On Fluidity Of Uhpc Mixture With High Volume Scmssupporting
confidence: 90%
“…The results have demonstrated that the addition of GO nanosheet reduced the flowability of UHPC mixture with high volume SCMs and thus its workability. Similar results were also reported in previous studies on NC [20,21], UHSC [22], self-compacting ultra-high-performance cement-based composites with high cement content [24], all containing GO nanosheets. Elsewhere, a previous study regarding UHPC enhanced with the graphite nanoplatelet (GNP), which is another type of graphene-based nanosheet (GNS), indicated that when GNP content was less than 0.05%, the flowability of the UHPC increased, whereas it decreased when the GNP content was greater than 0.05%, suggesting the flowability of the UHPC is affected by the dosages of both the high range water reducer and the GNP [30].…”
Section: Effect Of Go Nanosheets On Fluidity Of Uhpc Mixture With High Volume Scmssupporting
confidence: 90%
See 2 more Smart Citations
“…Mokhtar et al [18] reported that the addition of GO nanoplatelets (0.02% bwoc) to cement pastes increased the compressive strength by about 13%, and the addition of GO nanoplatelets (0.03% bwoc) to cement pastes increased the splitting tensile strength by 41%. Wu et al [19] reported that the compressive strength of the concrete curing for 28 days increased from 12.84% to 34.08%, while the content of the GO nanosheets increased from 0.02% to 0.08% with a water–binder ratio of 0.5. The addition of GO nanosheets improved the flexural strength of concrete from 2.77% to 15.60% at 28 days when the content of GO nanosheets increased from 0.02% to 0.08%.…”
Section: Introductionmentioning
confidence: 99%